Colon Cancer and Perturbations of the Sphingolipid Metabolism - Machala, Miroslav; Procházková, Jiřina; Hofmanová, Jiřina; Králiková, Lucie; Slavík, Josef; Tylichová, Zuzana; Ovesná, Petra; Kozubík, Alois; Vondráček, Jan (International journal of molecular sciences, 2019)
The development and progression of colorectal cancer (CRC), a major cause of cancer-related death in the western world, is accompanied with alterations of sphingolipid (SL) composition in colon tumors. A number of enzymes involved in the SL metabolism have been found to be deregulated in human colon tumors, in experimental rodent studies, and in human colon cancer cells in vitro. Therefore, the enzymatic pathways that modulate SL levels have received a significant attention, due to their possible contribution to CRC development, or as potential therapeutic targets. Many of these enzymes are associated with an increased sphingosine-1-phosphate/ceramide ratio, which is in turn linked with increased colon cancer cell survival, proliferation and cancer progression. Nevertheless, more attention should also be paid to the more complex SLs, including specific glycosphingolipids, such as lactosylceramides, which can be also deregulated during CRC development. In this review, we focus on the potential roles of individual SLs/SL metabolism enzymes in colon cancer, as well as on the pros and cons of employing the current in vitro models of colon cancer cells for lipidomic studies investigating the SL metabolism in CRC.
Keywords: neutrální ceramidasa; Lactosylceramides; regulace genové exprese u nádorů; Tumor Cells, Cultured; kyselá ceramidasa; modely nemocí na zvířatech; Humans; lysofosfolipidy; sfingosin-N-acyltransferasa; zvířata; Colonic Neoplasms; Disease Models, Animal; Sphingosine; Sphingolipids; protoonkogenní proteiny c-akt; sfingosin; Proto-Oncogene Proteins c-akt; nádorové buňky kultivované; Phosphotransferases (Alcohol Group Acceptor); laktosylceramidy; Neutral Ceramidase; Sphingosine N-Acyltransferase; Ceramides; Gene Expression Regulation, Neoplastic; Acid Ceramidase; nádory tračníku; ceramidy; Alkaline Ceramidase; Animals; alkalická ceramidasa; lidé; metabolismus lipidů; Lysophospholipids; Lipid Metabolism; fosfotransferasy s alkoholovou skupinou jako akceptorem; sfingolipidy